Tipologi Resepsi Taḥfīẓ Al-Qur’ān di Kalangan Mahasiswi IIQ Jakarta - Mamluatun Nafisah (ILMU USHULUDDIN, 2019)
This paper discusses the typology of the reception of taḥfīẓ al-Qur’ān among IIQ Jakarta students. This paper departs from the diversity of one's motivation in memorizing the Qur’an. Especially, in recent years, many television programs have appeared on the program taḥfīẓ al-Qur’ān. The skills of children in memorizing the verses of the newspaper simultaneously enliven the universe of social media, thus encouraging parents’ enthusiasm to form their children as hāfiẓ/ah. Various motivations certainly become their own color. To find out the typology of their reception of the taḥfīẓ al-Qur’ān, the author uses a phenomenological analysis approach that was conceived by Edmund Husserl. The results of this study concluded that Jakarta IIQ female students were reception taḥfīẓ al-Qur’ān functionally, aesthetically, and exegetically. Various receptions conducted by Jakarta IIQ students when viewed from outside the structure shows that IIQ Jakarta students are very religious. They make taḥfīẓ the Qur’ān as the main routine in their daily activities. Meanwhile, when viewed from its structure, it contains the message of the truth of miracles kalām Allāh and the guarantee of the owner of His words for people who memorize the Qur’ān based on the logic of pragmatic epistemology.